Special Section Introduction - Roberts, John H. and Lilien, Gary L. (Marketing Science, 2008)
We introduce the work of the finalists in the 2006 ISMS Practice Prize Competition, representing outstanding examples of rigor plus relevance in our profession. The winner, describing a collaboration between J.D. Power and Associates and U.C. Riverside, involves a sequenced program of research to understand the effect of promotional activity in the U.S. automobile market. The other three finalists address a model to calibrate the effects of corporate brand activity across three divisions at Allstate Insurance; a method for using CLV models to focus customer contact strategies at IBM; and a segmentation strategy to protect and gain customers in the face of a new entrant for the Austrian mobile telecommunications carrier, tele.ring.
https://katalog.adlr.link/Record/ai-55-aHR0cHM6Ly93d3cuanN0b3Iub3JnL3N0YWJsZS80MDA1NzEwNw